Insights into the late Cenozoic structural deformation and tectonic stress field of the Qiabuqia region, Gonghe Basin, northeastern Qinghai–Tibetan Plateau - Yang, Zhang; Qingda, Feng; Fucheng, Li; Linyou, Zhang; Chao, Zhang; Senqi, Zhang; Dunpeng, Li; Zhen, Yan; Jian, Song; Lei, Fu; Zhaoxuan, Niu (Frontiers in Earth Science, 2023)
During the late Cenozoic, along with the overall uplift of the northeastern Qinghai–Tibet Plateau, three stages of deformational history can be identified in areas surrounding the Waliguan Mountain, east of Gonghe basin, northeastern Qinghai-Tibetan plateau. In detail, these three stages include: (i) the late Miocene to late Pliocene, the deformation regime was dominated by the thrust napping with dextral strike-slipping; (ii) the early Pleistocene to the middle period of late Pleistocene, fault structures were dominated by the dextral strike-slipping with thrust napping; and (iii) the late period of late Pleistocene to middle Holocene, the thrust napping slowed down and finally braked, and meanwhile shallow surface began to loose and extend at the rear-edge Qiabuqia region. The drilling data of the DR4 borehole indicates the buried depth of the Xiangshuihe Formation is about ~1000 m (with a buried depth of ~1000 m) the tectonic stress in the top section of the Xianshuihe Formation is characterized with the normal fault-type (NF) tectonic stress, whereas the deep basement behaves as thrust fault-type (TF) and strike-slip type (SS) tectonic stress. In the top part of the Xianshuihe Formation, the maximum principal stress (σ1) is perpendicular and the minimum principal tectonic stress (σ3) is horizontal. Meanwhile, in the deep basement of the Xianshuihe Formation, the direction of σ1 is in the NE–SW direction, ranging from 20.1° to 75.3° with an average of 40.0°. Based on the above observations, three sets of hidden faults in the basement of the Qiabuqia region can be inferred, which are: (i) the NW–NNW trending compressional–torsional faults; (ii) the NE-trending tensional–torsional faults; and (iii) the NWW-trending compressional–torsional faults. These findings in this study can potentially offer a robust geological basis for the exploration and utilization of hot dry rock resource within the Gonghe basin.